Rhabdomyolysis with myoglobin-induced acute kidney injury: A case series of four cases - Hanock Unni Samuel; T Balasubramaniyan; S Thirumavalavan; C Vasudevan; R P Senthil Kumar; V Murugesan; Anila Abraham (Wolters Kluwer Medknow Publications, 2021)
Rhabdomyolysis is a potentially life-threatening clinical syndrome characterized by the breakdown of skeletal muscle cells and release of creatine kinase (CK), lactate dehydrogenase (LDH), and myoglobin into the plasma and interstitial space. Rhabdomyolysis can occur due to a variety of causes and acute kidney injury (AKI) is one of its most dreaded complications occurring in 33%-50% patients. The main pathophysiology of renal injury is due to vasoconstriction, intraluminal casts, tubular obstruction, and direct myoglobin toxicity. As the symptoms are nonspecific, a high level of suspicion is required in the mind of the treating physician. Early diagnosis and prompt management with fluid resuscitation, initiation of renal replacement therapy (RRT), and elimination of causative agents can help prevent complications. We hereby report four interesting cases of this clinical syndrome with emphasis on the causative agents.